Effect of Creative Productive Learning Model Assisted by Visual Media and Learning Inquiry Model with Media Assistance Concept Map on Student Learning Outcomes in Science Subjects in Class V SD Negeri 7 Poso - Doranggi, Selvina; Hatibe, Amiruddin; Mustapa, Kasmudin (Universitas Tadulako, 2017)
This study aimed to determine the Effect of Creative Productive Learning Model Assisted by Visual Media and Learning Inquiry Model with Media Assistance Concept Map on Student Learning Outcomes in Science Subjects in Class V SD Negeri 7 Poso. This research was an experimental research. The population was the seventh grade students of SD Negeri 7 Poso amounting to 50 students, the samples used as the source of research data were the Va class students amounted to 25 students and Vb class amounted to 25 students. The data collection methods conducted in this study was the students' test result. Data analysis techniques used in this study included hypothesis prerequisite test and hypothesis testing. The results of the first hypothesis with SPSS program obtained significant value for t test results of 18.728 was greater than t table of 2.064 and the value of p = 0,000 <0.05 so that the alternative hypothesis states that there is influence of productive creative learning model assisted visual media to the learning outcomes students of Grade V of SD Negeri 7 Poso on Science subjects (Natural Science) was accepted. The result of second hypothesis calculation with SPSS program got significant value for result of test of t test equal to 19,316 bigger than t table equal to 2,064 and value p = 0,000 <0,05 so alternative hypothesis that there is influence of model of inquiry learning inquiry media concept map to learning result students of Grade V of SD Negeri 7 Poso on Science subjects (Natural Science) was accepted. The results of the third hypothesis with SPSS program obtained Fcount value of 12.292 larger than F tabel of 4.043 and the value of p = 0.001 <0.05 so that the alternative hypothesis states that there is influence of creative learning model assisted visual media and inquiry learning model assisted media concept map simultaneous to the result of learning of grade V of SD Negeri 7 Poso on science subject (Natural Science) was accepted.